1997
DOI: 10.1177/096032719701600601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating chemical risks: results of a survey of the British Toxicology Society

Abstract: 1 Members of the British Toxicology Society partici pated in a survey to determine their attitudes, beliefs, and perceptions regarding risks from chemicals. Similar surveys had previously been conducted with toxicologists and members of the general public in the United States and Canada. Data from 312 completed questionnaires were analyzed. 2 In general, the British toxicologists judged risks to be quite low for most hazards, with the exception of cigarette smoking and asbestos. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 7 publications
5
42
0
1
Order By: Relevance
“…However, Barke et al, (1997) have found that female physical scientists judge risks from nuclear technologies to be higher than do male physical scientists. Similar results with scientists were obtained by Slovic et al, (1997) who found that female members of the British Toxicological Society were far more likely than male toxicologists to judge societal risks as moderate or high. Certainly the female scientists in these studies cannot be accused of lacking knowledge and technological literacy.…”
Section: Sexsupporting
confidence: 85%
“…However, Barke et al, (1997) have found that female physical scientists judge risks from nuclear technologies to be higher than do male physical scientists. Similar results with scientists were obtained by Slovic et al, (1997) who found that female members of the British Toxicological Society were far more likely than male toxicologists to judge societal risks as moderate or high. Certainly the female scientists in these studies cannot be accused of lacking knowledge and technological literacy.…”
Section: Sexsupporting
confidence: 85%
“…Sociopolitical factors, such as gender and employment, have been found to affect the risk perception of scientists, and research has demonstrated that attitudinal differences exist between scientists working in industry and those in academic settings (Slovic et al 1997;Slovic 1999). Key variables for this study included whether climate scientists working for federal agencies had a different perspective than those in a university setting and whether academic training, research orientation, age, or political views affected their views about policy initiatives to reduce GHGs.…”
Section: Are Climate Scientists a Homogeneous Set Of Actors?mentioning
confidence: 98%
“…The effect of a number of explanatory factors on risk perception is thus studied: typically, these include socio-economic and demographic characteristics of the involved population, popular attitudes about uncertain events, and concerns about the ongoing risk scenario. [Slovic et al, 1990;Alhakam and Slovic, 1994;Slovic et al,1997;Slovic, 1999;Sjoberg, 1998Sjoberg, , 2000 In our comparative analysis, we looked into differences between studies in the way they model popular risk perception, with the aim of investigating their causality direction with respect to WTPs. This information is captured by the RISKPERC variable (Table 5).…”
Section: The Monetary Valuationmentioning
confidence: 99%